2004
DOI: 10.1002/ajpa.10410
|View full text |Cite
|
Sign up to set email alerts
|

Test of revised method of age estimation from the auricular surface of the ilium

Abstract: The objective of this paper is to test a revised method of age estimation based on the morphology of the auricular surface recently proposed by Buckberry and Chamberlain ([2002] Am. J. Phys. Anthropol. 119:231-239). The study sample consists of 309 individuals of known sex, age, and race from the Terry and Huntington Collections. Auricular surfaces were scored using the revised technique to determine whether it is equally applicable to both sexes as well as blacks and whites. The auricular surfaces of the same… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
76
1
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(87 citation statements)
references
References 10 publications
7
76
1
3
Order By: Relevance
“…The Spanish sample demonstrates lower levels of bias and absolute error than the Thai sample used by Schmitt [2], the Canadian sample of Saunders et al [4] and the Italian sample of Hens et al [10] for the Lovejoy and Suchey-Brooks methods. It also shows lower bias and absolute error than the U.S. sample of Mulhern and Jones [30] for the Buckberry and Chamberlain method.…”
Section: ) the Applicability Of The Methods To Spanish Skeletal Sammentioning
confidence: 76%
See 1 more Smart Citation
“…The Spanish sample demonstrates lower levels of bias and absolute error than the Thai sample used by Schmitt [2], the Canadian sample of Saunders et al [4] and the Italian sample of Hens et al [10] for the Lovejoy and Suchey-Brooks methods. It also shows lower bias and absolute error than the U.S. sample of Mulhern and Jones [30] for the Buckberry and Chamberlain method.…”
Section: ) the Applicability Of The Methods To Spanish Skeletal Sammentioning
confidence: 76%
“…In this method, each auricular surface feature is analyzed and scored independently and then combined into a composite score related to a broad age range. This method is the most recent of the three, and although some authors have proposed modifications [26,29]; it has rarely been evaluated using documented osteological collections [30].…”
Section: Introductionmentioning
confidence: 99%
“…Unsurprisingly, given the old demography of the Spitalfields reference sample, the vast majority of these studies have found that the Buckberry-Chamberlain method performs better on older individuals (Falys et al 2006;Gocha et al 2015;Hens and Belcastro 2012;Mulhern and Jones 2005;San Millán et al 2013). Indeed, the equal age-at-death distribution used in the study by Mulhern and Jones (2005) presumably will have reduced biases created by the uneven age-at-death distribution in the original paper. The descriptive statistics reported in this study are therefore potentially preferable to those reported in Buckberry and Chamberlain (2002), particularly when calculating inaccuracy and bias.…”
Section: Figure 2 Herementioning
confidence: 99%
“…However, when the method has been tested on different populations, bias and inaccuracy, based on the mean ages derived from, and reflecting the structure of, the Spitalfields population are commonly used (Falys et al 2006;Gocha et al 2015;Hens and Belcastro 2012;Moraitis et al 2014;Mulhern and Jones 2005;Rissech et al 2012;San Millán et al 2013). Unsurprisingly, given the old demography of the Spitalfields reference sample, the vast majority of these studies have found that the Buckberry-Chamberlain method performs better on older individuals (Falys et al 2006;Gocha et al 2015;Hens and Belcastro 2012;Mulhern and Jones 2005;San Millán et al 2013). Indeed, the equal age-at-death distribution used in the study by Mulhern and Jones (2005) presumably will have reduced biases created by the uneven age-at-death distribution in the original paper.…”
Section: Figure 2 Herementioning
confidence: 99%
“…When methods based on, for example, the pubic symphysis [51][52][53][54][55][56] and auricular surface [57][58][59][60][61] are considered, it is clear that their mean errors are also high. It seems that age estimation in adults still remains challenging, and that the Lamendin and modified Lamendin techniques are probably on par with other methods used in adult age estimation.…”
Section: Discussionmentioning
confidence: 99%